2003
DOI: 10.1086/379322
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Rotavirus-Associated Deaths, Using New Molecular Diagnostics

Abstract: Rotavirus, the most common cause of severe, dehydrating gastroenteritis among children worldwide, annually causes approximately 500,000 deaths among children aged <5 years. The primary site of rotavirus infection is the small intestine. Pathologic investigations of patients who died of rotavirus infection are limited to data from a few reported autopsies, and dehydration with electrolyte imbalance is believed to be the major cause of death. Several recent reports suggest that children who died during a rotavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 28 publications
6
40
1
3
Order By: Relevance
“…Two of the three children had rotavirus RNA in extraintestinal tissues (spleen, heart, lung, kidney, testes, bladder, adrenal gland, and pancreas), as determined by reverse transcription-PCR. Confirmation of positive PCR products by hybridization with serotype-specific probes indicated that the two children with extraintestinal rotavirus were infected with different G serotypes (47). These findings show that viral antigen and/or virus particles enter the circulation.…”
Section: Systemic Infection With Rotavirusmentioning
confidence: 72%
“…Two of the three children had rotavirus RNA in extraintestinal tissues (spleen, heart, lung, kidney, testes, bladder, adrenal gland, and pancreas), as determined by reverse transcription-PCR. Confirmation of positive PCR products by hybridization with serotype-specific probes indicated that the two children with extraintestinal rotavirus were infected with different G serotypes (47). These findings show that viral antigen and/or virus particles enter the circulation.…”
Section: Systemic Infection With Rotavirusmentioning
confidence: 72%
“…The role of rotavirus in upper respiratory tract infections of children requires additional study, as does the presence of rotavirus viremia in children and its possible consequence related to detection of HRV in the cerebrospinal fluid of children with central nervous system disease (16,38). The diarrhea associated with rotavirus typically lasts from 2 to 8 days, but immunodeficiency, immunosuppression, and malnutrition are risk factors for severe and prolonged symptoms and chronic infection (9,16). The incidence of rotavirus infection is similar in both developed and developing countries, but the morbidity and mortality of the disease are much greater in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Reye's-like syndrome sometimes mimics Reye's syndrome in children with genetic defects of fatty acid oxidation. There are three reports of systemic rotavirus infection involving the central nervous system, all of which included elevated transaminase levels and lipid droplets in the liver (5,6,9). In these cases, analysis of amino acids and/or organic acids was normal.…”
Section: Case Reportmentioning
confidence: 99%
“…In these cases, analysis of amino acids and/or organic acids was normal. In two of the three cases, the patients had a history of chickenpox 2 weeks before admission (6,9). Mitochondrial functional analysis was undertaken in another two cases and was normal (5,6).…”
Section: Case Reportmentioning
confidence: 99%